Effects of antiretroviral resistance on outcomes and health care resource utilisation among people with HIV in the United States and Europe: a real-world survey - Mary J. Christoph; Megan Chen; Seojin Park; Woodie Zachry; Cassidy Trom; Will Ambler; Fritha Hennessy; Hannah Jones; Tim Holbrook (HIV Research & Clinical Practice, 2025)
Background: Despite advances in antiretroviral therapy (ART), resistance remains a barrier to effective HIV treatment. Objective: This study evaluated associations between ART drug resistance and treatment adherence, health care resource utilisation (HCRU), and quality of life (QoL) among people with HIV. Methods: A retrospective, observational study was conducted using the Adelphi HIV Disease Specific Programme™ (DSP) between 2021 and 2023 across the United States and Europe. Data were collected via physician surveys, patient record forms, and patient self-completion forms. Results: Data for 2006 people with HIV and resistance testing were contributed by 290 physicians, and 586 people with HIV provided patient data. Overall, 286 people with HIV (14%) had documented resistance. People with HIV with resistance had received more ART regimens than those without resistance (p < 0.0001) and had lower viral suppression rates (p = 0.004) and lower CD4 counts (p = 0.032). People with HIV with resistance reported lower treatment adherence (p = 0.017) but similar QoL compared to those without resistance. People with HIV with resistance also had significantly more HIV-related hospitalisations than those without resistance (p = 0.022). Conclusions: ART resistance was associated with higher HCRU and poorer health outcomes in people with HIV, underscoring the need for continued focus on adherence and resistance management.